On 10-Centralizer Groups of Odd Order. (1st April 2014) - Foruzanfar, Z.; Mostaghim, Z.
Abstract : Let G be a group, and let Cent ( G ) denote the number of distinct centralizers of its elements. A group G is called n -centralizer if C e n t ( G ) = n . In this paper, we investigate the structure of finite groups of odd order with C e n t ( G ) = 10 and prove that there is no finite nonabelian group of odd order with C e n t ( G ) = 10 .